Transmigration - Eine Mobilitätsstudie in einer Herkunftsregion - Heigl, Andreas; Schwarz, Joachim (ERDKUNDE, 2000)
The study examines the factors influencing the decision to migrate among potential transmigrants in Indonesia. Consideration is given to the economic incentives and the influences of cultural and social values on the Javanese in this process. Transmigration is a possibility for landless and poor Javanese to improve their living conditions. It competes with alternative forms of migration or even with trying to escape from deprivation without moving from the place of abode. The theoretical approach integrates several macro- and microlevel theories as network- and value expactancy models. They all have something significant to say about the transmigration process, but none of them explains it satisfactory. It is therefor necessary to use an integrated model which is based on the microlevel (motivations, values and expectations), but also includes important external factors such as the macro structure of the region of origin, political implications and social networks. The study demonstrates that the motivating factors in the decision to migrate are different between rural and urban transmigrants. In rural areas transmigration appears to families of potential transmigrants to offer a good means of improving their living conditions. Local cultural ties, however, act as a restraint, and the existence of social networks in the region of destination and the willingness of relatives or neighbours to migrate are necessary before a decision to migrate is made. In urban areas, the role of Transmigration Offices is much more important in convincing or forcing individuals or families to take part in the transmigration program, as urban people do not like to work in agriculture. In today’s economic crisis especially in urban areas transmigration seems to be even more attractive for a lot of Javanese people despite the problems of integration in the areas of destination.